Effects of the interactions between platelets with other cells in tumor growth and progression - Li, Yaxin; Wang, Haiyan; Zhao, Zhen; Yang, Yuanming; Meng, Zifan; Qin, Lifeng (Frontiers in Immunology, 2023)
It has been confirmed that platelets play a key role in tumorigenesis. Tumor-activated platelets can recruit blood cells and immune cells to migrate, establish an inflammatory tumor microenvironment at the sites of primary and metastatic tumors. On the other hand, they can also promote the differentiation of mesenchymal cells, which can accelerate the proliferation, genesis and migration of blood vessels. The role of platelets in tumors has been well studied. However, a growing number of studies suggest that interactions between platelets and immune cells (e.g., dendritic cells, natural killer cells, monocytes, and red blood cells) also play an important role in tumorigenesis and tumor development. In this review, we summarize the major cells that are closely associated with platelets and discuss the essential role of the interaction between platelets with these cells in tumorigenesis and tumor development.